Health benefits to the pediatric population from reduction of ambient particulate matter in Krakow, Poland - Agnieszka Pac; Renata Majewska; Natalia Nidecka; Elzbieta Sochacka-Tatara; Frederica P Perera (Environmental Research Letters, 2024)
There have been few assessments of the health benefits to children of policies aimed at curbing fossil fuel-related air pollution. This has resulted in a lack of awareness regarding their positive impact on the health of this vulnerable population. We estimated the pediatric health benefits of policies targeting coal burning in one of Europe’s most polluted cities, Kraków, Poland. We combined available data on child health outcomes, related concentration-response functions, childhood population counts, and concentrations of PM _2.5 and PM _10 based on city-wide air monitoring in Kraków. Two exposure reduction scenarios were examined. First, we used the observed decrease in air pollutant concentrations between 2010 and 2019. Second, we hypothesized a reduction to the annual World Health Organization (WHO) air quality guideline values issued in 2005. Between 2010 and 2019, the mean annual air pollution levels in Kraków decreased for both PM _2.5 and PM _10 . Annual average PM _2.5 concentrations declined by 39.1%, reaching 23.3 μ g m ^−3 ; PM _10 dropped by 39.2% to 34.6 μ g m ^−3 . These reductions in air pollution can be linked to numerous actions undertaken at local and national levels. We estimate that the forgone benefits in 2010 from not having achieved the PM levels observed in 2019 (on an annual basis) included: 505 (35.7%) fewer incident cases of asthma in the 1–14 age group, 81 fewer preterm births (16.8% decrease), 52 fewer cases of low birth weight (12.3% decrease), and 59 avoided asthma hospitalizations in 0–18 year olds. Compliance with the 2005 WHO PM _2.5 guidelines in 2010 would have avoided 780 incident asthma cases in the 1–14 age group (54.5% decrease), 138 preterm births (28.3% decrease), and 90 cases of low birth weight (21.2% reduction) and 219 (54.2%) fewer asthma hospitalizations in 0–18 year olds. Large health benefits were also estimated for PM _10 in both scenarios. This study estimated substantial health benefits for children in Kraków, which were largely attributable to clean air policies that restrict the use of coal and other solid fuels. Kraków provides a model for other cities in Europe and beyond that are affected by coal pollution and have high rates of preterm birth, low birth weight, and respiratory illness.